Surgical management for mesenteric cysts in pediatric patients: a single center experience - Gafar, Ahmed M.; Batikhe, Mohamed Y. (International Surgery Journal, 2018)
Background: Mesenteric cysts are exceptional abdominal lesions of childhood. Presentation may vary with broad spectrum of symptoms from asymptomatic mass and nonspecific complaints to an acute abdomen. Objectives of this study were to present a series of patients with mesenteric cysts and to analyze our experience with emphasis on the presentation, management, and outcome. Methods: This observational study included thirteen children were diagnosed and treated for mesenteric cysts. All cases subjected to clinical evaluation, laboratory investigations and radiological studies. The diagnosis was confirmed on laparotomy. Ethics committee approval was obtained. The main data which extracted and analyzed included demographic data, operative finding, postoperative complications and duration of hospital stay. Data were analyzed using SPSS for Windows software and P value of ≤ 0.05 was considered significant. Results: There were 13 patients with mesenteric cyst, 5 girls and 8 boys. The ages ranged from neonate to 8 years. Abdominal mass and pain was the main presenting symptoms. Prenatal diagnosis established in two cases. Laparotomy performed in all cases. Small bowel mesentery is the commonest site. Two patients required urgent surgery. Surgical procedures included cyst excision with or without intestinal resection. Chylolymphatic cyst was documented in 4 cases. Post-operative complications reported in 2 cases. Conclusions: Mesenteric cysts are unusual in children with variable clinical presentation. Complete excision was feasible in nearly all cases, bringing a favorable outcome. The possibility of this disease entity should be considered as the cause of acute abdomen.